OPTIMIZATION OF AGRARIAN REFORM POLICIES IN TRANSMIGRATION AREAS IN THE PROVINCE OF GORONTALO - Kusno Katili; Arifin Tahir; Zuchri Abdussamad; Yanti Aneta (Adisam Publisher, 2025)
This study aims to evaluate the factors influencing the optimization of Agrarian Reform Policies in transmigration areas, specifically focusing on skills, education, and adaptation capabilities. The research data were collected through interviews and direct observations in the transmigration locations. The findings indicate that while the three analyzed factors are relatively adequate, there is still room for improvement. In terms of skills, it was observed that transmigrants' proficiency in modern agricultural techniques remains suboptimal. This is primarily due to the continued employment of outdated methods in training programs. Regarding education, a salient challenge pertains to the limited accessibility of primary and secondary education for transmigrant children who reside in distant locations and encounter inadequate road conditions. Another salient challenge relates to agrarian education programs, where replacement heads of households frequently lack awareness of procedures for acquiring Land Ownership Certificates (SHM) through land ownership. Regarding adaptability, transmigrants still require guidance from mentors, facilitators, or community assistance programs that can help them apply newly acquired knowledge and skills. The government and relevant stakeholders must actively provide the necessary support to facilitate the adaptation process. By doing so, transmigrants can integrate effectively, fostering a harmonious and productive relationship between transmigrants and the local community.